Term recognition from electronic medical records of Singaporean hospital (1/2) - Muhammad Hafiz Mohamed Hassan (2014)
Doctors at Hospitals daily write reports on patients’ statuses and kept them for future usages. However, with the increase use in computers to store information and analysed data, there have been problems allowing doctors to freely express their diagnosis and get the system to analyse the content of what is written. The challenge also lies with trying to tie down the medical terms used by the experience doctors in Singapore especially, with the standard terms that are used by other doctors, in different parts of the world.